LncRNA ENST869 Targeting Nestin Transcriptional Region to Affect the Pharmacological Effects of Chidamide in Breast Cancer Cells - Feng, Xiuyan; Han, Han; Guo, Yarui; Feng, Xue; Guo, Shanchun; Zhou, Weiqiang (Frontiers in Oncology, 2022)
Breast cancer is one of the leading threats to women's health today. Its incidence rate and mortality rate are ranked first. Although progress has been made in the development and application of anti-breast cancer drugs, the problem of drug resistance that limits the effective application has not been well resolved. The purpose of this study is to explore the behavior strategy of positive LncRNA in the process of Chidamide breast cancer therapy. We utilized human breast cancer MCF-7 or MDA-MB-231 cells as the research objects, and conducted RNA library screening and sequencing comparative analysis through high-throughput sequencing. The binding of positive LncRNA and its downstream target genes in RNA and protein levels were tested. The results showed that the expression of LncRNA ENST869 in Chidamide treatment increased significantly, and real-time PCR and cell viability assay confirmed this deduction. RNAplex analysis pointed out that LncRNA ENST869 and Nestin mRNA may interact. RNA interference and western blot detected that LncRNA ENST869 could target and regulate the expression of Nestin. Luciferase assay and RNA-protein pulldown showed that LncRNA ENST869 was mainly reflected in affecting Nestin transcription. There might be a highly active binding region of LncRNA ENST869 regulating Nestin transcriptional activity within 250 bp upstream of Nestin transcription’s starting point. In addition, LncRNA ENST869 did not directly interact with Nestin protein to affect its activity. In conclusion, our experiments confirmed that the expression of LncRNA ENST869 could influence downstream Nestin function in the process of Chidamide treatment, and Nestin as a key player in influencing the pharmacological activity of Chidamide and might be an essential factor and a novel biomarker in drug resistance of breast cancer cells.